2015
DOI: 10.1088/1612-2011/13/1/015001
|View full text |Cite
|
Sign up to set email alerts
|

High-energy room-temperature Fe2+:ZnS laser

Abstract: Characteristics of a room temperature laser on polycrystalline ZnS:Fe2+ subjected to diffuse doping from two sides were investigated. The sample was pumped by a non-chain electrodischarge HF laser with the FWHM duration of the radiation pulse of ~140 ns. The diameter of the pumping radiation spot on the surface of the crystal was 3.8 mm. Further increases in the size of the pumping spot were limited by parasitic generation arising due to a high concentration of Fe ions in the near-surface layer of the sample a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 31 publications
4
39
0
Order By: Relevance
“…Further energy scaling in a longer KTA crystal would be expected with sacrifice of reduced bandwidth. Nevertheless, this 2.2–5.0 μ m broadband pulse can seed a Fe 2+ :ZnSe CPA laser 48 , 49 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Further energy scaling in a longer KTA crystal would be expected with sacrifice of reduced bandwidth. Nevertheless, this 2.2–5.0 μ m broadband pulse can seed a Fe 2+ :ZnSe CPA laser 48 , 49 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…The energy level 5 D of the Fe 2+ ion splits into two levels, 5 E and 5 T 2 and it is suggested that the transition 5 T 2 → 5 E can be used for the mid‐IR laser oscillation similar to Fe 2+ :ZnSe and Fe 2+ :ZnS . Compared with Fe‐doped chalcogenides, polycrystalline Fe 2+ :MgAl 2 O 4 ceramic gain medium can possess a higher volume of active ions due to the absence of the thermal diffusion process of iron from the surface of the sample to a depth of ~1.5 mm at a doping concentration of ~10 19 cm −3 …”
Section: Introductionmentioning
confidence: 99%
“…However, the major challenge is achieving the transmission to the close theoretical density >99.9% and retaining the grain size as less as possible to attain superior optical and mechanical properties. Although, previous researchers have studied optical and structural properties of IR transparent polycrystalline ZnS and other ceramics, only few studies are reported room temperature electrical properties, and no report is found on high temperature (500oC) impedance spectroscopic studies [4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%